UNDERRATED MYTHOLOGY OF THE UNDERRATED—REFLECTIONS ON ZBIGNIEW HERBERT’S THE KING OF THE ANTS OR A TRAGIC ATTEMPT TO TAME THE CRUELTY OF GODS - Jurkowski, Jakub Andrzej (Colloquia Litteraria, 2019)
The article sketchily surveys Zbigniew Herbert’s mythological prose texts from Król Mrówek, which remained unpublished during his lifetime. A suite of analytical and interpretive considerations intends to present Herbert as an author who took up the task of investigating the consistency of the Mediterranean myth. The article applies twentieth-century mythology studies tools to situate Herbert’s book within literary tradition. In his apocrypha Herbert subjects mythological tradition to a renarration; he shows appreciation for characters traditionally devoid of the grace to speak and reinstates their hitherto deformed human faces. Simultaneously, Herbert undermines the inevitability, necessity, and permanence of the verdicts of the fate which, in traditionally narrated mythology, stands as the final instance bringing back the cosmic order.